1994
DOI: 10.1037/0022-006x.62.2.306
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of recurrent abdominal pain in children: A controlled comparison of cognitive-behavioral family intervention and standard pediatric care.

Abstract: This study describes the results of a controlled clinical trial involving 44 7-to 14-year-old children with recurrent abdominal pain who were randomly allocated to either cognitive-behavioral family intervention (CBFI) or standard pediatric care (SPC). Both treatment conditions resulted in significant improvements on measures of pain intensity and pain behavior. However, the children receiving CBFI had a higher rate of complete elimination of pain, lower levels of relapse at 6-and 12-month follow-up, and lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
205
0
11

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(223 citation statements)
references
References 41 publications
7
205
0
11
Order By: Relevance
“…The most extensively described CBT program for managing RAP is the one developed by Sanders et al (19,23). Several other narrative reviews and descriptions of CBT for recurrent pain are available (17,26).…”
Section: Common Components Of a Cbt Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The most extensively described CBT program for managing RAP is the one developed by Sanders et al (19,23). Several other narrative reviews and descriptions of CBT for recurrent pain are available (17,26).…”
Section: Common Components Of a Cbt Programmentioning
confidence: 99%
“…The goal is to minimize parental attention given to pain and to support the child in applying coping skills. For example, in the program by Sanders et al (19,23), parents are taught to reinforce (give attention to) well behaviour, respond to complaints of pain by encouraging the child to engage in an alternate activity (distraction), ignore nonverbal pain behaviour, avoid modelling pain behaviour, and learn to distinguish between RAP and other physical complaints that may require medical intervention.…”
Section: Common Components Of a Cbt Programmentioning
confidence: 99%
“…6,7 The effectiveness of psychological therapies for pediatric FAP has been studied in several randomized controlled trials (RCTs). [8][9][10][11][12][13] Although a recent Cochrane review described cognitive behavior therapy (CBT) as a promising psychological treatment, this review also underscored that many RCTs have considerable methodological drawbacks such as small sample sizes and high dropout rates. 14 Moreover, a well-designed RCT published after the Cochrane review did not provide unequivocal evidence for the benefit of CBT because it showed CBT to be superior to a control condition but only according to parent report of the child' s pain, not according to child-reported pain.…”
mentioning
confidence: 99%
“…In the present study, the parents of children with somatic complaints were poorly educated and the trends support that Somatization was more associated with lower education [11][12][13]. In our study, parents of Somatizing children were mainly in lower occupations and even unemployed.…”
Section: Discussionmentioning
confidence: 76%